AN ANALYSIS OF LOCUTIONARY AND ILLOCUTIONARY ACTS IN SAMPOERNA A MILD’S TVADVERTISEMENT - RIDLWAN, AHMAD (Jurnal Ilmiah Mahasiswa FIB, 2013)
Advertisement presents or describes a product interestingly which could make people very desirable to purchase or consume. The researcher is interested in analyzing A Mild TV advertisement; because this advertisement is the pioneer of cigarette advertisement which is usually presented with trendy and attractive way for introducing the product.  This research entitled “An Analysis of Locutionary and Illocutionary Acts in Sampoerna A Mild’s TV Advertisement” is aimed at analyzing the speech act of A Mild TV advertisements in 2012. The researcher uses pragmatics theory. Yule (1996, p. 3) “Pragmatics is the study of speaker meaning”. It can be said that a word or phrase in every utterance coming out of speaker or writer has a meaning. Actually, context influences several aspects of circumstances such as places, time, and with whom they are talking to. In this case, it is speech act. Speech act is about how the speaker performed in saying something, how the locutor (speaker/writer) offers an apology, greeting, request, complaint, invitation, compliment, or refusal to the interlocutor (listener/reader). In speech act there are three kinds of acts: Locutionary act, Illocutionary act, and Perlocutionary act. Locutionary act is speech act of saying something of the utterance, the act of saying something in the full sense of say. Meanwhile illocutionary act is the act performed in saying something and a perlocutionary act is the act performed as a result of saying. Key words: Advertisement, A Mild, Pragmatics, Locutionary and Illocutionary Acts.